A new record of kelp Lessonia spicata (Suhr) Santelices in the Sub-Antarctic Channels: implications for the conservation of the "huiro negro" in the Chilean coast - Rosenfeld, Sebastian; Mendez, Fabio; Calderon, Martha S.; Bahamonde, Francisco; Pablo Rodriguez, Juan; Ojeda Villarroel, Jaime Andrés; Marambio Gallardo, Johanna Valeska; Gorny, Matthias; Mansilla Muñoz, Andres Omar (My University, 2019)
The Katalalixar National Reserve (KNR) lies in an isolated marine protected area of Magellan Sub-Antarctic channels, which represent an important area for marine biodiversity and macroalgal conservation. The present study is the first report of the species Lessonia spicata, "huiro negro", in the Magellan Sub-Antarctic channels. This finding has implications for macroalgal biogeography and conservation concerns in the Chilean coast. In the ecological assessments of the KNR in 2018 we found populations of L. spicata, specifically on rocky shores of Torpedo Island and Castillo Channel. The morphological identification and molecular phylogeny based on nuclear (ITS1) sequences revealed that these populations of Lessonia are within the lineage of L. spicata of central Chile. This report increases the species richness of kelps for the Magellan Sub-Antarctic Channels from two to three confirmed species (L. flavicans, L. searlesiana and L. spicata), and it also extends the southern distribution range of L. spicata. This species has high harvest demand and is moving towards southern Chile; thus, these populations should be considered as essential for macroalgal conservation in high latitudes of South America.
Keywords: conservation; extension; biogeography; kelp; sub-antarctic; magellan